Influence of NaOH content on the alkali conversion mechanism in MSWI bottom ash alkali-activated mortars. (10th July 2020) - Huang, Guodong; Yang, Ke; Sun, Yuhua; Lu, Zeyang; Zhang, Xingyu; Zuo, Lin; Feng, Yongqi; Qian, Ruochun; Qi, Yue; Ji, Yongsheng; Xu, Zhishan
Highlights: The insufficient NaOH content (<1.8%) affected the conversion from free alkali to union alkali. High alkalinity environment (13.5 < pH < 14.5) promotes the formation of polymerization products. Excessive addition of NaOH (above 5.6%) cannot further promote the transformation from free alkali to union alkali. Abstract: This is a microscopic analysis of the promoting effect that different NaOH contents exerted on both polymerization reaction and alkali conversion mechanism between free and union alkali. The study focuses on the strength development of municipal solid waste incineration bottom ash (BA) alkali-activated mortars. Mixing with the appropriate amount of NaOH (between 1.8% and 5.6%) formed a good alkalinity stimulating environment (13.5 < pH < 14.5) in alkali-activated samples and promoted the process of polymerization. Moreover the formation of high-strength polymerization products (C-A-S-H and C-S-H gels) was also promoted, which significantly facilitated the conversion from free alkali to union alkali and increased the compressive strength. However, excessive addition of NaOH (above 5.6%) cannot further promote the transformation from free alkali to union alkali and decrease the compressive strength. The polymerization and formation of silicate (C-S-H gels) were severely affected by the high alkalinity environment (pH > 14.5) and the excess active sodium competed with active calcium for active silicon and aluminium. This resulted in a large number of low strength N-A-S-H gels formation, while the yield of high strength C-S-H gels decreased significantly.